Non-sexist language: A proposal to combat gender violence and produce wellbeing in the classroom (Papeles, 2023)
The recognition and visibilization of women through inclusive language that is promoted in the classroom as a full right to generate equitable environments is a challenge that must be taken up by teachers. The objective of the proposed research is oriented to show how the linguistic resources that teachers can use in their daily work in the classroom through the written and verbal word help to combat gender violence associated with women's right to difference and equality. The methodology is based on a bibliographic and documentary research that serves as the basis for the application of quantitative data collection instruments applied to 91 students and 8 tutors of community practices. The research findings show that the language used reproduces inequalities between women and men, and encourages the assignment of professional roles marked by gender, which unconsciously influences women to enter certain professional fields. Teachers have in their classrooms the opportunity to build spaces free of gender violence using the powerful tool of the spoken and written word.
Keywords: education; Gender-based violence; Non-sexist language; Ecuador